MANAGEMENT EFFICIENCY, ENTERPRISE MANAGEMENT EFFICIENCY CRITERIA (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
To assess the effectiveness of the activities of the enterprise, first of all, economic indicators are used. The main thing is the ratio of profit to total costs in the reporting period. If deviations or unsatisfactory results are detected, a factor analysis is performed to determine the exact causes.